Evaluation of the biocompatibility and skin hydration potential of vitamin E-loaded lipid nanosystems formulations: in vitro and human in vivo studies - Vaz, S. (2021)
Lipid-based nanosystems, such as nanostructured lipid carriers (NLC) and nanoemulsions (NE) have been described as promising alternatives to conventional formulations for increase skin hydration. Besides, these systems have been used as efficient vehicles for lipophilic molecules that improve skin properties (e.g. vitamin E). In this study, we performed comparative investigations between hydrogels formulations containing vitamin E-loaded NLC (HG-NLCVE) and vitamin E-loaded nanoemulsion (HG-NEVE). The experiments started with particle size measurements, which showed no significant differences between nanoparticles/nanodroplets sizes after incorporation in the hydrogel net (386 nm vs. 397 nm for HG-NLCVE and 402 nm vs. 514 nm for HG-NEVE). Afterwards, in vitro biocompatibility studies in human keratinocytes were carried out, being observed that the lipid-based nanosystems were more cytotoxic for the cells before incorporation in the hydrogel. Finally, the formulations hydration potential and sensory attributes for skin application were evaluated by in vitro occlusion tests and in vivo human experiments. The results showed that the HG-NLCVE exhibited the best occlusive properties, whereas the HG-NEVE performed a faster skin hydration effect. Furthermore, the latter was selected as the most attractive for skin application, although the HG-NLCVE was described as more suitable to obtain a long-lasting effect. This study demonstrated the in vitro and in vivo safety and hydration potential of hydrogels containing vitamin E-loaded lipid-based nanosystems. These results establish a basis to assess the cutaneous use of these systems, despite more in vivo experiments, for longer periods and in more volunteers, are required before commercialization.